Redundant let‐7a suppresses the immunomodulatory properties of BMSCs by inhibiting the Fas/FasL system in osteoporosis. Issue 4 (5th January 2018) - Liao, Li; Yu, Yang; Shao, Bingyi; Su, Xiaoxia; Wang, Han; Kuang, Huijuan; Jing, Huan; Situai, Yi; Yang, Deqin; Jin, Yan
Abstract : Bone marrow‐derived mesenchymal stem cell (BMSC) cytotherapy has emerged as a promising treatment strategy for refractory immune diseases; however, the influence of the pathologic conditions of donors on the immunomodulatory properties of BMSCs is still poorly understand. Here, we found that BMSCs that were derived from donors with osteoporosis were ineffective as cytotherapy for patients with experimental colitis and graft‐vs.‐host disease (GVHD). In vivo and in vitro assays revealed that the capacity of osteoporotic BMSCs to induce T‐cell apoptosis declined as a result of decreased Fas and FasL protein. Additional analysis revealed that let‐7a, a micro‐RNA induced by TNF‐α in osteoporosis, inhibited the expression of the Fas/FasL system via post‐transcriptional regulation. By knocking down let‐7a expression, we successfully recovered the immunosuppressive capacity of osteoporotic BMSCs and improved their therapy for experimental colitis and GVHD. Taken together, our study demonstrates that the immunomodulatory properties of BMSCs are suppressed in osteoporosis and illustrates the molecular mechanism that underlies this suppression. These findings might have important implications for the development of targeted strategies to improve BMSC cytotherapy.— Liao, L., Yu, Y., Shao, B., Su, X., Wang, H., Kuang, H., Jing, H., Shuai, Y., Yang, D., Jin, Y. Redundant let‐7a suppresses the immunomodulatory properties of BMSCs by inhibiting the Fas/FasL system in osteoporosis. FASEB J. 32, 1982–1992 (2018). www.fasebj.org